2013
DOI: 10.1111/jipb.12063
|View full text |Cite
|
Sign up to set email alerts
|

Cotton AnnGh3 Encoding an Annexin Protein is Preferentially Expressed in Fibers and Promotes Initiation and Elongation of Leaf Trichomes in Transgenic Arabidopsis

Abstract: The annexins are a multifamily of calcium-regulated phospholipid-binding proteins. To investigate the roles of annexins in fiber development, four genes encoding putative annexin proteins were isolated from cotton (Gossypium hirsutum) and designated AnnGh3, AnnGh4, AnnGh5, and AnnGh6. Quantitative reverse transcription-polymerase chain reaction (qRT-PCR) results indicated that AnnGh3, AnnGh4, and AnnGh5 were preferentially expressed in fibers, while the transcripts of AnnGh6 were predominantly accumulated in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 57 publications
0
13
1
Order By: Relevance
“…In this study, we found that GhAnn1 is preferentially expressed both in vegetative and reproductive tissues (Fig. 4), which is different from the cotton annexins reported previously that are expressed and function preferentially in cotton fibers (Huang et al 2013;Li et al 2013). Further expression analysis showed that GhAnn1 is upregulated by diverse abiotic stresses and phytohormones (Fig.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In this study, we found that GhAnn1 is preferentially expressed both in vegetative and reproductive tissues (Fig. 4), which is different from the cotton annexins reported previously that are expressed and function preferentially in cotton fibers (Huang et al 2013;Li et al 2013). Further expression analysis showed that GhAnn1 is upregulated by diverse abiotic stresses and phytohormones (Fig.…”
Section: Discussioncontrasting
confidence: 64%
“…3), whether expressed in onion in vivo or tobacco in vitro. The location is differs from AnnGh3, which is found in the cytoplasm (Li et al 2013), and AnxGb6, which localizes to the plasma membrane and nucleolus (Huang et al 2013). The plasma membrane is a key interface between plant cells and their environment, which play key roles in mediating responses to the endogenous and environmental cues that regulate various developmental and metabolic events (Barbara and Christian 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Transgenic cotton seedlings overexpressing AnnBj1 and GhAnn1 both showed welldeveloped root systems with significantly enhanced root length under salt and drought stress (Divya et al, 2010;Zhang et al, 2015a). AnnGh3, which is preferentially expressed in fibers, promotes the initiation and elongation of leaf trichomes (Li et al, 2013b). Ectopic AnxGb6 in Arabidopsis enhanced root elongation, and more F-actin accumulated in the basal part of the root cell elongation zone.…”
mentioning
confidence: 99%
“…Research in strawberry indicates that Annfaf may be involved in the ripening progress of strawberry fruit (Chen et al, 2016). AnnGh5 has been described to be preferentially expressed in fibers and is mainly accumulated in rapidly elongating fibers (Li et al, 2013). As FtANX1 is grouped into Group II together with AnnMt1, Annfaf, and AnnGh5, we suspect that FtANX1 might have similar functions and be involved in cell signaling and ripening processes.…”
Section: Discussionmentioning
confidence: 99%